2012
DOI: 10.1371/journal.pone.0051533
|View full text |Cite
|
Sign up to set email alerts
|

Novel PAX9 and COL1A2 Missense Mutations Causing Tooth Agenesis and OI/DGI without Skeletal Abnormalities

Abstract: Inherited dentin defects are classified into three types of dentinogenesis imperfecta (DGI) and two types of dentin dysplasia (DD). The genetic etiology of DD-I is unknown. Defects in dentin sialophosphoprotein (DSPP) cause DD type II and DGI types II and III. DGI type I is the oral manifestation of osteogenesis imperfecta (OI), a systemic disease typically caused by defects in COL1A1 or COL1A2. Mutations in MSX1, PAX9, AXIN2, EDA and WNT10A can cause non-syndromic familial tooth agenesis. In this study a simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Song et al () reported eight families with exclusion mutations in the DSP region; they found mutations in the DPP region in five families, while the remaining three families showed no pathogenic mutations. Wang et al () found a mutation in COL1A2 in a DGI family without bone defects, and they suggested that COL1A1 and COL1A2 should be considered candidate genes in isolated DGI cases without a DSPP mutation. However, we found several polymorphisms, but no pathogenic mutations, in these two genes in Family E. Plausible explanations include other genes responsible for these dentin defects (whole‐exon sequencing could be used to investigate new underlying genes); polymorphisms may mitigate a defect when they appear together (this possibility could be investigated using in vitro assays and/or animal experiments); and copy number variation may lead to the occurrence and development of disease to some degree (Almal and Padh, ).…”
Section: Discussionmentioning
confidence: 99%
“…Song et al () reported eight families with exclusion mutations in the DSP region; they found mutations in the DPP region in five families, while the remaining three families showed no pathogenic mutations. Wang et al () found a mutation in COL1A2 in a DGI family without bone defects, and they suggested that COL1A1 and COL1A2 should be considered candidate genes in isolated DGI cases without a DSPP mutation. However, we found several polymorphisms, but no pathogenic mutations, in these two genes in Family E. Plausible explanations include other genes responsible for these dentin defects (whole‐exon sequencing could be used to investigate new underlying genes); polymorphisms may mitigate a defect when they appear together (this possibility could be investigated using in vitro assays and/or animal experiments); and copy number variation may lead to the occurrence and development of disease to some degree (Almal and Padh, ).…”
Section: Discussionmentioning
confidence: 99%
“…A female patient with OI type IV in our cohort had DGI, no missing teeth, and a COL1A2 missense mutation, c.1171G>A, p.(Gly391Ser), reported previously in a male patient of European origin (Wang et al , ) with both DGI and tooth agenesis. He had agenesis of ten teeth while his mother had agenesis of four teeth and no DGI.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, in a recent paper, Wang et al . described a family with tooth agenesis in whom isolated dentin defects occurred only in the proband. Mutational analysis of candidate genes revealed a novel PAX9 mutation causing hypodontia and a novel COL1A2 mutation causing only dentin defects .…”
Section: Discussionmentioning
confidence: 99%